2022
DOI: 10.3389/fcell.2022.844342
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Stiffness and TGFβ2 Regulate YAP/TAZ Activity in Human Trabecular Meshwork Cells

Abstract: Primary open-angle glaucoma progression is associated with increased human trabecular meshwork (HTM) stiffness and elevated transforming growth factor beta 2 (TGFβ2) levels in the aqueous humor. Increased transcriptional activity of Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ), central players in mechanotransduction, are implicated in glaucomatous HTM cell dysfunction. Yet, the detailed mechanisms underlying YAP/TAZ modulation in HTM cells in response to alterations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 88 publications
7
50
0
Order By: Relevance
“…Importantly, this can be accomplished under both normal and simulated glaucomatous conditions (32)(33)(34). We previously demonstrated the bidirectional responsiveness of the HTM hydrogel to pathologic TGFb2 induction (35) and ROCKi rescue using standard Y27632 (14) for correlative analyses of TM cell cytoskeletal organization with tissue-level functional changes (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, this can be accomplished under both normal and simulated glaucomatous conditions (32)(33)(34). We previously demonstrated the bidirectional responsiveness of the HTM hydrogel to pathologic TGFb2 induction (35) and ROCKi rescue using standard Y27632 (14) for correlative analyses of TM cell cytoskeletal organization with tissue-level functional changes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Human donor eye tissue use was approved by the SUNY Upstate Medical University Institutional Review Board (protocol #1211036), and all experiments were performed in accordance with the tenets of the Declaration of Helsinki for the use of human tissue. Primary human TM (HTM) cells were isolated from healthy donor corneal rims discarded after transplant surgery, as previously described (32)(33)(34), and cultured according to established protocols (37,38). Three normal HTM cell strains (HTM05 [Male/57], HTM07 [Male/39], HTM36 [Female/56]) were used for the experiments in this study.…”
Section: Htm Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…During the onset of glaucoma, the elevation in IOP causes ischemia, hypoxia, and oxidative stress accumulation in the retina, all of which contribute to the apoptosis of RGCs [ 60 ]; AH outflow resistance is determined in particular by the ECM [ 64 ]. Along with increased protein deposition (mainly collagen and elastin), the ECM becomes more dense and stiff, which leads to an increase in IOP [ 65 ]. Many ECM-stimulating factors are found to be upregulated in glaucoma, including TGF-β2 in the AH and actin secreted by trabecular cells [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…YAP/TAZ transcriptional activity elevation is associated with TM cell dysfunction. It has been found that the YAP/TAZ nuclear localization was increased in the glaucomatous HTM cells compared to the normal HTM cells [18]. This study aimed to investigate the regulatory effect of YAP/TAZ on the fibrotic activity of HTM cells and their potential as biomarkers for fibrotic activity.…”
Section: Introductionmentioning
confidence: 99%